5 higher education marketing trends to embrace in 2022. Issue 5 (7th January 2022) - Talarico, Donna
Abstract : As we settle into 2022, this month's column will take a look at predicted marketing trends for the new year, both in general and those specific to higher education. Consider the following marketing trends, and how they might be applicable to your recruitment techniques: